Healthcare system encounters before COPD diagnosis: a registry-based longitudinal cohort study. Issue 2 (8th November 2019) - Johnson, Kate M; Khakban, Amir; Bryan, Stirling; Sin, Don D; Sadatsafavi, Mohsen
Abstract : Background: There is high interest in strategies for improving early detection of chronic obstructive pulmonary disease (COPD). These strategies often rely on opportunistic encounters between patients with undiagnosed COPD and the healthcare system; however, the frequency of these encounters is currently unknown. Methods: We used administrative health data for the province of British Columbia, Canada, from 1996 to 2015. We identified patients with COPD using a validated case definition, and assessed their visits to pharmacists, primary care and specialist physicians in the 5 years prior to the initial diagnosis of COPD. We used generalised linear models to compare the rate of outpatient visits between COPD and non-COPD comparator subjects matched on age, sex and socioeconomic status. Results: We assessed 112 635 COPD and non-COPD pairs (mean 68.6 years, 51.0% male). Patients with COPD interacted with pharmacists most frequently in the 5 years before diagnosis (mean 14.09, IQR 4–17 visits/year), followed by primary care (10.29, IQR 4–13 visits/year) and specialist (8.11, IQR 2–11 visits/year) physicians. In the 2 years prior to diagnosis, 72.1% of patients with COPD had a respiratory-related primary care visit that did not result in a COPD diagnosis. Compared with non-COPD subjects, patients with COPD had higher rates of primary care (rate ratio (RR) 1.40, 95% CI 1.39 to 1.41), specialist (RR 1.35, 95% CI 1.34 to 1.37) and pharmacist (RR 1.62, 95% CI 1.60 to 1.63) encounters. Conclusions: Patients with COPD used higher rates of outpatient services before diagnosis than non-COPD subjects. Case detection technologies implemented in pharmacy or primary care settings have opportunities to diagnose COPD earlier.